ANALISIS KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PASCA PEMBELAJARAN DARING - Endah Meida Supiani; Dani Firmansyah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was conducted to analyze and describe student learning independence in learning mathematics after online learning that students have experienced for approximately two years. This study used a qualitative approach and descriptive method by taking as many as 33 students in class VIII L of SMP Negeri 1 Karawang Barat as subjects as subjects. The instrument used is a non-test in the form of a questionnaire which contains 20 statement items and has 5 indicators. The data that has been collected from the questionnaire is then analyzed and described using the criteria of the percentage of student answers. The results of the study show that some students have learning independence in learning mathematics after online learning by 69.15%. So that it can be said that most students have good independence in learning mathematics after good learning. Even so, it is better for a student to increase independence in learning mathematics to achieve even better learning outcomes.